Nitric Oxide Donor Administration For improvement of Uterine Blood Flow in Unexplained Recurrent Pregnancy Loss - Mazen A. El-Zahry (Al-Azhar University, Faculty of Medicine (Damietta), 2021)
Background: Recurrent pregnancy loss is still a challenging obstetric condition.  It linked to impaired uterine blood, and vasodilators seem to prevent recurrent pregnancy loss. The aim of the work: The current study aimed to compare between investigate the Doppler uterine artery indices in females with recurrent pregnancy loss [unexplained]. It also aimed to study the effect of intravaginal isosorbide mononitrate, on the pattern of uterine blood flow. Materials and Methods: This observational, nested case control study had been completed at Al-Azhar University Hospitals.  Two groups of females [each 50 females] were studied. The control group [females with no previous pregnancy loss and have a viable child or more]. The study group [females with history of unexplained recurrent pregnancy loss]. Vaginal color Doppler ultrasound was done to assess pulsation and resistance indices of uterine arteries in the mid-luteal phase of the cycle. Then, 20 mg of isosorbide mononitrate was applied vaginally and measurement of the vascular indices were registered after two hours again. Both groups were compared and the effect of isosorbide mononitrate on the uterine artery vascular indices the study group was documented. Results: Higher uterine artery resistance and pulsation indices are noticed in females with recurrent pregnancy. A significant reduction in these indices was found after vaginal application of Isosorbide mononitrate. Both groups were comparable regarding patient demographics. Doppler indices were significantly lower in control than study group. The endometrial thickness was negatively correlated with right RI and left PI (r = -0.328, -0.342, p = 0.039 and 0.031, respectively).   Conclusion: Poor uterine perfusion is associated with spontaneous abortion. The vaginal application of isosorbide mononitrate, nitric oxide donor could be an effective treatment for the correction of uterine vasculature in patients with recurrent pregnancy loss.